Diagnostic utility of maximum vertical pocket versus amniotic fluid index in assessing amniotic fluid volume for the prediction of adverse maternal and fetal outcomes: a systematic review and meta-analysis. (17th November 2021) - Sekhon, Subhjit; Rosenbloom, Joshua I.; Doering, Michelle; Conner, Shayna N.; Macones, George A.; Colditz, Graham A.; Tuuli, Methodius G.; Carter, Ebony B.
Abstract: Objective: To compare the utility of maximum vertical pocket versus amniotic fluid index for predicting adverse perinatal outcomes. Methods: Systematic review of randomized clinical studies comparing these two ultrasound techniques and random-effects meta-analysis to quantify a range of perinatal outcomes. Result: Six studies with 4278 women were eligible. Use of the maximum vertical pocket reduced the rate of diagnosis of oligohydramnios (pooled relative risk 0.38; 95% confidence interval 0.27, 0.53). Use of the maximum vertical pocket was associated with significantly lower rates of non-reassuring fetal heart tracing, cesarean delivery for fetal distress, and induction of labor for oligohydramnios. There were no differences in the rates of cesarean delivery, presence of meconium, umbilical artery pH <7.1, 5-minute Apgar score <7, or admission to the neonatal intensive care unit. Conclusion: The use of maximum vertical pocket is associated with a lower rate of pregnancy intervention without any worsening of adverse pregnancy outcomes.